Principles of Marketing. - Kotler, Philip; Armstrong, Gary (Gary M.); Balasubramanian, Sridhar; Kotler, Philip (2024)
'Principles of Marketing' helps readers master today's key marketing challenge: to create vibrant, interactive communities of consumers who make products and brands an integral part of their daily lives. To help individuals understand how to create value and build customer relationships, Kotler and Armstrong present fundamental marketing information within an innovative customer-value framework.
Previous edition: published as by Philip Kotler, Gary Armstrong, with Marc Oliver Opresnik. 2021.
Includes bibliographical references and index.
Keywords: Marketing; Business and Management